2012
DOI: 10.1166/jnn.2012.6707
|View full text |Cite
|
Sign up to set email alerts
|

Selective Effect of Procaine, Tetracaine and Dibucaine on Gold Nanoparticles

Abstract: An aqueous colloid dispersion of gold nanoparticles (AuNPs) was prepared by reduction of gold(III) chloride and its interaction with three local anesthetics (procaine, dibucaine or tetracaine) was investigated. Optical spectra reveal the modifications in the absorption band of nanoparticles related to their self assembly mediated by anesthetic molecules and depending on the progress in time of the aggregation process. TEM images show the features of the self assemblies formed by the association of gold nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
0
18
1
Order By: Relevance
“…However, this interaction did not induce size and zeta potential changes to the nanoparticles when subjected to 10 μM tetracaine (data not shown). This was unlike the results obtained by Mocanu et al, 39 who observed a decrease in zeta potential values when nanoparticles were mixed with tetracaine molecules. The difference in the results was probably due to the different concentrations investigated.…”
Section: ■ Discussioncontrasting
confidence: 99%
“…However, this interaction did not induce size and zeta potential changes to the nanoparticles when subjected to 10 μM tetracaine (data not shown). This was unlike the results obtained by Mocanu et al, 39 who observed a decrease in zeta potential values when nanoparticles were mixed with tetracaine molecules. The difference in the results was probably due to the different concentrations investigated.…”
Section: ■ Discussioncontrasting
confidence: 99%
“…As discussed elsewhere, 35 the investigated anesthetic molecule tertiary amines (Figure 1) all have a tertiary nitrogen atom and another basic nitrogen atom: primary in procaine ( Figure 1A), secondary in tetracaine ( Figure 1C), and quinoline aromatic in dibucaine ( Figure 1B). The two pK a values, for the two steps of dissociation from the dicationic form BH 2 2+ to the monocationic BH + , respectively, from this to the neutral form (B) are between 8.8 and 9 for the tertiary nitrogen in procaine, and between 2.0 and 2.3 for its −NH 2 group.…”
mentioning
confidence: 62%
“…However, there were some differences in the effect of the three anesthetics on the AgNPs, so one should assume that specific interactions between these organic molecules and the NPs must also play a role in the self-assembly of AgNPs mediated by these molecules. As in the case of citrate-capped gold NPs, 35 the formation of hydrogen bonds should be considered, …”
mentioning
confidence: 99%
“…Gold nanoparticles are also of particular interest for science, nanotechnology and medical applications [121]. This is due to its ability to bind to biomolecules such as amino acids [122][123][124][125][126][127][128], anesthetics [129], chemotherapeutic drugs [130,131], and proteins [132][133][134][135]. GNPs and silymarin was observed to improve liver function and reduced cholestasis.…”
Section: Silymarin Interaction With Metallic Nanoparticlesmentioning
confidence: 99%